OspA Sequence Comparison and Protection Against Borrelia burgdorferi Infection in Gerbils by Recombinant OspA Protein - A Karami; P Hindersson; N Høiby; S Morovvati (Tehran University of Medical Sciences, 2006)
Lyme borreliosis is a tick-born disease caused by the spirochete Borrelia burgdorferi. The aim of this research was molecular typing of different strains of B. burgdorferi and protective efficacy of outer surface protein in animal model. Seven strains of B. burgdorferi isolated from skin and CSF of Lyme disease patients were compared using PCR- RFLP as well as DNA and amino acid sequences. The gene coding for Outer Surface Protein A (OspA) was cloned and recombinant protein was expressed. Immunization experiment was conducted on gerbils with purified recombinant OspA protein. The OspA gene sequence of B. afzelii and B. garinii showed 83.76% similarity and calculated amino acid identity of 84 % with each other and 82.5% similarity to B31 strain. DK6 was 100% similar to Pbi, 99.6 % to Ptrob isolate and 88 % to B31 strain. Cloning and expression of OspA from DK6 strain in E. coli has shown lipoprotein with molecular weight of 32 kDa. Immuno blot of recombinant protein from DK6 with rabbit anti DK1 revealed strong reaction with OspA from DK6 strain. Immunization experiment in gerbils with three doses of rOspA protein revealed that all immunized animals either with OspA fusion protein alone or combined with adjuvant were protected against infection with DK1 or DK6 pathogenic strains.